Experiences of food access for asylum seekers who have ceased using a food bank in Melbourne, Australia. Issue 8 (7th August 2018) - McKay, Fiona H.; Bugden, Megan; Dunn, Matthew; Bazerghi, Chantelle
Abstract : Purpose: The purpose of this paper is to explore the experiences of asylum seekers who were entitled to use a foodbank but who had ceased attending the service, to understand why they were not using the charity, and to investigate their food-related experiences. Design/methodology/approach: This study employed a mixed-method approach utilising telephone interviews. Interviews were conducted with 70 asylum seekers in Melbourne, Australia, between September 2015 and February 2016. Interviews explored food-related settlement experiences, food insecurity and experiences of hunger. Findings: Two-thirds of participants were identified as experiencing food insecurity. Despite food and financial insecurity, participants were not using the foodbank as frequently as they were entitled as: the food was not culturally or religiously appropriate to them; asylum seekers with income felt uncomfortable taking food from others who were perceived to be in greater need; or because they were experiencing transport barriers. Participants also experienced a range of physical and mental health concerns. Originality/value: Ensuring asylum seekers have access to culturally appropriate foods and services is essential. However, given the diversity in foodbank membership, it may not be feasible to provide all of the desired foods at no cost; instead, increased access to culturally appropriate foods may be achieved through a subsidy programme. Novel or alternative approaches to community engagement and food distribution may be needed to increase food security and to decrease hunger in this group.